2022
DOI: 10.1038/s41467-021-27935-9
|View full text |Cite
|
Sign up to set email alerts
|

Retinal pigment epithelium-specific CLIC4 mutant is a mouse model of dry age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is the leading cause of blindness among the elderly. Dry AMD has unclear etiology and no treatment. Lipid-rich drusen are the hallmark of dry AMD. An AMD mouse model and insights into drusenogenesis are keys to better understanding of this disease. Chloride intracellular channel 4 (CLIC4) is a pleomorphic protein regulating diverse biological functions. Here we show that retinal pigment epithelium (RPE)-specific Clic4 knockout mice exhibit a full spectrum of functional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 83 publications
(94 reference statements)
1
12
0
Order By: Relevance
“…In addition, DR animals had visual acuity changes i.e., decrease the in SFT value in the OMR test and increase in the number of errors in the PM test. Similar results were reported [47,48]. The retinal tissue biomarkers in DR-induced animals were altered i.e., increased level of LDH and NSE and decreased the level of catalase activity, in congruent with the findings of other studies [7,49].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, DR animals had visual acuity changes i.e., decrease the in SFT value in the OMR test and increase in the number of errors in the PM test. Similar results were reported [47,48]. The retinal tissue biomarkers in DR-induced animals were altered i.e., increased level of LDH and NSE and decreased the level of catalase activity, in congruent with the findings of other studies [7,49].…”
Section: Discussionsupporting
confidence: 91%
“…3E and 3F). Accumulation of lipofuscin-laden pigmented microglia/macrophages in the subretinal space have also been observed in other AMD mouse models [40][41][42] and aged WT mice. 43 Furthermore, complement activation in the RPE is another key feature of AMD in humans 44,45 and also found in some mouse models.…”
Section: Gpx4 Cko Mice Mimic Clinicopathological Features Of Human Amdmentioning
confidence: 64%
“…CX3CR1 -deficient mice have been reported to show prolonged presence of microglial cells (MC) in the subretinal space suggesting excessive photoreceptor OS phagocytosis by subretinal MC which subsequently accumulated SDD (Chuang et al, 2022). In the current study, SDD close to EN was characteristically observed in Cldn1 deficient mice.…”
Section: Discussionmentioning
confidence: 99%